Initial Study on Thatched Roofing Assembly Ignition Vulnerabilities to Firebrand Showers - Suzuki, Sayaka (Fire Saf J, 2019)
Structures fitted with thatched roofing assemblies are prone to ignition during the course of large outdoor fires. Experiments with thatched roofing assemblies were performed by using a reduced-scale continuous-feed firebrand generator in a wind facility to investigate fundamental ignition mechanisms. The wind speed was varied from 3 m/s to 6 m/s to observe the ignition and flame spread of thatched roofing assemblies. It was observed that firebrands penetrated into the thatched roofing assembly, sometimes unseen from the outside, resulting in ignition and ultimately rapid flame penetration. Information obtained in this study would be useful to evaluate and develop effective counter measures to protect historical structures with thatched roofing assemblies, especially for historical buildings, such as The United Nations Educational, Scientific and Cultural Organization (UNESCO)’s world heritage sites in Japan.